Seismic stratigraphic analysis for hydrocarbon exploration in the Beta Field, Coastal Swamp Depobelt, Niger Delta - Adeleye, Mutiu Adesina; Yekeen, Kazeem Oladayo; Amidu, Sikiru Adetona (Geology, Geophysics and Environment, 2020)
Hydrocarbon exploration analysis from a seismic stratigraphic approach was carried out within the Beta Field, Coastal Swamp Depobelt, Niger Delta, to identify system tracts and sequence boundaries that could be associated with potential hydrocarbon accumulation. 3D seismic volume and data from four wells were analyzed. Depositional sequences, system tracts, sequence boundaries, and candidate maximum flooding surfaces were picked from logs, while reflection patterns and terminations were interpreted from seismic sections. Log shapes from gamma rays in combination with seismic facies analysis were interpreted in order to delineate lithology, depositional environments and depositional sequences. Seismic attributes were extracted and were draped on gridded surfaces from the interpreted seismic horizons. These were integrated with structure maps to obtain structural and stratigraphic trends, and the possible presence of reservoir sand. Five depositional sequences and nine seismic facies were identified within the field. The depositional sequences were designated Sequences S1 to S5 based on the depth of the occurrences and stacking patterns. This study reveals a progression from fluvial depositional settings to the shelf. The main reservoirs identified are the sand units of the highstand and lowstand within three depositional sequences (S1, S4 and S5) although interbedded sands within the TST of S4 and S5 are also suspected of being potential reservoirs. The channel sand deposits within the study area are suspected to be hydrocarbon bearing as they occurred within the complex fault trapping system popular in the Niger Delta. The application of seismic stratigraphy, as shown in this study, serves to encourage exploration in the Niger Delta where it could be effectively employed for reducing risk in hydrocarbon exploration.